Role of Augmented Reality, Virtual Reality and Streaming Services in the Field of Education (2020–2023) – A Systematic Review - Pineda-Torres, Eliseo Walter (2025)
This paper systematically reviews the demand for real-time streaming services in the education sector over the period 2020–2023. The systematic review analyzes the effects of augmented reality (AR) and virtual reality (VR) in education, focusing on the need for real-time streaming services. These technologies have grown significantly in education, enabling collaborative and immersive experiences. VR, supported by leading streaming platforms, has facilitated distance education, especially during the COVID-19 pandemic. The methodology was based on searching for articles in databases such as Ebsco, Springer, IEEE, ScienceDirect, and Scopus. Inclusion and exclusion criteria were applied, creating a final sample of 60 papers, with a geographical distri-bution highlighting the important role of China and the United States. The results indicate that changes in education, the focus on VR, and the impact of the COVID-19 pandemic are the main drivers of demand for educational streaming. This led to a rapid adoption of online educational platforms. Challenges to implementing streaming services include a lack of training in educa-tional institutions and a lack of practice in certain areas. Content customization, video quality, and adequate technological infrastructure are the most sought-after functionalities by users.